Crosslinking type polyaspartic acid vapor phase corrosion inhibitor and product thereof
Through the network structure of crosslinked polyaspartic acid gas-phase corrosion inhibitor, the existing gas-phase anti-rust packaging materials have solved the poor isolation performance and material toxicity of the water vapor and material in humid environments, and achieved efficient and environmentally friendly metal materials rust prevention Effect.
Patent Information
- Application Number
- CN202411264449.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-03
AI Technical Summary
The existing gas-phase anti-rust packaging materials have poor performance in isolation of water vapor in humid environments, resulting in a short protection period of metal materials. The commonly used gas-phase corrosion inhibitors are toxic or have strong odor, and there is a risk of environmental pollution and human injury.
The crosslinked polyaspartic acid gas-phase corrosion inhibitor is used to form a network structure through the crosslinking of polyaspartic acid, benzotriazole, sodium benzoate, sodium citrate and soluble polyvalent metal salt crosslinking agent, as a gas-phase slower The corrosion agent and support load do not require additional sustained release carriers to achieve gas-phase corrosion inhibition and water-vapor isolation.
The anti-rust cycle is extended, the gas-phase corrosion inhibition ability is enhanced, water vapor is prevented from passing through anti-rust products, and the protection effect of metal materials is improved, while avoiding the environmental protection and safety risks of using high specific surface area loading materials.
Smart Images

Figure CN119243163A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of vapor phase rust prevention of metal materials, and in particular to a cross-linked polyaspartic acid vapor phase corrosion inhibitor and a product thereof. Background Art
[0002] Gas phase anti-rust packaging is widely used in the production, process, storage and transportation of metal materials due to its low cost, convenient operation, cleanliness and good corrosion inhibition effect. Gas phase corrosion inhibitors are the core materials of gas phase anti-rust packaging. Nitrite and aliphatic organic amine compounds are widely used. These compounds have good gas phase corrosion inhibition effects, but they have certain toxicity or strong odor, which can easily cause environmental pollution and human harm. Therefore, efficient, environmentally friendly and safe green gas phase corrosion inhibitors are the development trend in this field. Polyaspartic acid (PASP) is an amino acid polymer that exists in some mollusks. It is biodegradable and an environmentally friendly chemical. The structure of polyaspartic acid contains rich functional groups such as carbonyl, amino, and hydroxyl. It can be used as a metal corrosion inhibitor and has a good corrosion inhibition effect in an alkaline environment (pH>8). By compounding with benzotriazole, sodium benzoate, hexamethylenetetramine, urea and other reagents, the static weight loss method and gas phase identification and other experimental methods have verified its gas phase corrosion inhibition ability for metals such as carbon steel. The development of this type of bio-based degradable gas phase corrosion inhibitor to prepare gas phase rust-proof packaging materials is of great significance to the metal parts and equipment related industries.
[0003] Chinese patent CN117512598 discloses a vapor phase corrosion inhibitor for carbon steel in marine environment, which contains polyaspartic acid or its derivatives, sodium benzoate, 5-methylfurfurylamine, dimethylimidazole, and urea. The vapor phase corrosion inhibitor effectively improves the corrosion inhibition rate of carbon steel in marine atmospheric environment and prolongs its service life. Chinese patent CN109023379A also discloses a carbon steel vapor phase rust inhibitor, including polyaspartic acid, benzotriazole, sodium tungstate, urotropine, urea and water, which has excellent anti-rust performance for carbon steel. Chinese patent CN107653746B discloses an environmentally friendly vapor phase rust-proof paper, including an aerogel layer, a composite slow-release layer, and fiber paper, wherein the composite slow-release layer is between the aerogel layer and the fiber paper, and the components include sodium tungstate, phytic acid, urotropine, polyaspartic acid, urea, silicon dioxide, and organophosphorus degrading enzyme. Chinese patent CN106544677B discloses an environmentally friendly gas phase rust-proof fiberboard and a preparation method thereof. Polyaniline, phytic acid, triethanolamine borate, dicyclohexylamine octanoate, polyaspartic acid, and silicon dioxide are fully and uniformly mixed in a certain mass ratio, dispersed in deionized water, and the pH value is adjusted with ammonia water to prepare a gas phase corrosion inhibitor aqueous dispersion. The gas phase corrosion inhibitor aqueous solution is applied on the surface of a paper fiberboard by a coating machine, and dried in air to obtain a gas phase rust-proof fiberboard. Using a similar method, Chinese patent CN106637227B discloses an oleic acid hydroxyethyl imidazoline vapor phase anti-rust fiberboard, which uses oleic acid hydroxyethyl imidazoline, phytic acid, sodium cinnamate, sodium benzoate, polyaspartic acid, and silicon dioxide as a composite vapor phase corrosion inhibitor; CN106676536B discloses a lauric acid hydroxyethyl imidazoline vapor phase anti-rust fiberboard, which uses lauric acid hydroxyethyl imidazoline, phytic acid, sodium molybdate, sodium borate, polyaspartic acid, and silicon dioxide as a composite vapor phase corrosion inhibitor.
[0004] In the preparation process of these vapor phase anti-rust papers or fiberboards, compound polyaspartic acid vapor phase corrosion inhibitors are used, and high specific surface area load materials such as silicon dioxide are used. The purpose is to adsorb the vapor phase corrosion inhibitor and achieve a slow-release effect, so as to prevent the vapor phase corrosion inhibitor from volatilizing too quickly in a short period of time, resulting in a too short protection period for the metal material. In addition, in practical applications, especially in humid environments, such as during sea transportation, vapor phase anti-rust packaging materials need to withstand the influence of water vapor, while paper products and fiberboards are highly permeable and have poor water vapor isolation performance. They usually need to be used together with desiccants in the packaging materials to reflect better vapor phase corrosion inhibition capabilities. Therefore, it is of special value and significance to develop polyaspartic acid vapor phase corrosion inhibitors and their products that do not require the addition of additional load materials, isolate water vapor, and are environmentally safe. Summary of the invention
[0005] The purpose of the present invention is to provide a water vapor-isolating cross-linked polyaspartic acid vapor corrosion inhibitor without additional slow-release carriers and a vapor-phase rust-proof product thereof.
[0006] In a first aspect, the present invention provides a cross-linked polyaspartic acid vapor phase corrosion inhibitor, the vapor phase corrosion inhibitor comprising a vapor phase corrosion inhibition liquid and a cross-linking agent solution,
[0007] The raw materials for preparing the vapor phase corrosion inhibitor include the following components based on 100 parts by weight:
[0008] Sodium polyaspartate 10-50 parts
[0009] 1-5 parts of benzotriazole
[0010] Sodium benzoate 1-10 parts
[0011] Sodium citrate 1-10 parts
[0012] Water balance;
[0013] The cross-linking agent solution is a soluble divalent or trivalent metal salt solution.
[0014] Preferably, the metal in the soluble metal salt solution is any one of aluminum, calcium, barium and zinc, preferably calcium.
[0015] More preferably, the soluble metal salt solution is any one of calcium chloride solution, zinc chloride solution, barium chloride solution and aluminum chloride solution.
[0016] Preferably, the mass concentration of the soluble metal salt solution is 0.1-30%.
[0017] In the second aspect, the present invention provides a vapor phase rust-proof product based on the cross-linked polyaspartic acid vapor phase corrosion inhibitor described in the first aspect. On a substrate, a first coating is performed with a vapor phase corrosion inhibition liquid of the vapor phase corrosion inhibitor, and then a second coating is performed with a cross-linking agent solution and then dried to obtain the vapor phase rust-proof product.
[0018] Preferably, the substrate includes any one of kraft paper, paper tray, fiberboard, non-woven fabric, etc.
[0019] In a third aspect, the present invention further provides a method for preparing the vapor phase rust-proof product according to the second aspect, the method comprising the following steps:
[0020] S1, dissolving sodium polyaspartate, benzotriazole, sodium benzoate and sodium citrate in water by stirring to prepare a vapor phase corrosion inhibitor liquid, and setting aside;
[0021] S2, first coating: applying the first coating of the vapor phase corrosion inhibitor on the substrate;
[0022] S3, after the first coating is completed, a soluble metal salt solution is used as a cross-linking agent solution to perform a second coating on the surface of the vapor phase corrosion inhibition solution;
[0023] S4, after the second coating is completed, the vapor phase rust-proof product is naturally dried or baked, wherein the dry weight ratio of the vapor phase corrosion inhibitor solution to the crosslinking agent solution is 10-20:1, and the total coating amount of the two is 10-30g / m 2 , more preferably 15g / m 2 .
[0024] Preferably, the first coating is performed by any of dipping, rolling, spraying, and shower coating.
[0025] Preferably, the second coating is performed by spraying or shower coating.
[0026] In a fourth aspect, the present invention further provides use of the vapor phase rust-proof product described in the second aspect in rust prevention of metal materials.
[0027] Compared with the prior art, the advantages of the present invention are:
[0028] Due to the ionic action of the carboxyl anions of the polyaspartic acid in the vapor phase corrosion inhibitor solution and the multivalent positive ions in the cross-linking agent solution, a network structure is formed, that is, polyaspartic acid is both a vapor phase corrosion inhibitor component and a supporting load carrier after cross-linking, and other components in the vapor phase corrosion inhibitor solution such as benzotriazole, sodium benzoate, and sodium citrate can be loaded therein, without adding porous or nano-loaded materials that play a slow-release role, the corrosion inhibition effect of the vapor phase corrosion inhibitor can be exerted, and the anti-rust cycle can be extended. At the same time, the cross-linked polyaspartic acid vapor phase corrosion inhibition layer has a strong bonding force with the substrate after coating and drying, and the vapor phase corrosion inhibitor components, paper substrate debris, etc. are not easy to fall off from the surface of the product, polluting the internal product. In addition, the network structure of the vapor phase rust-proof product formed by the technical solution of the present invention has a large cross-linking density and strong compactness, which can prevent water vapor from penetrating the vapor phase rust-proof product to reach the internal metal material, thereby improving the vapor phase corrosion inhibition ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Schematic diagram of the preparation of cross-linked polyaspartic acid vapor phase corrosion inhibitor and its products.
[0030] Figure 2 The surface morphology of the vapor phase corrosion inhibition layer of the anti-rust paper product obtained based on the vapor phase corrosion inhibitor in Example 1 (A) and Example 2 (B) of the present invention.
[0031] Figure 3 The anti-rust effects of the carbon steel test sample (A) wrapped with kraft paper as the substrate and the carbon steel test sample (B) wrapped with the anti-rust paper product obtained by the vapor phase corrosion inhibitor of Example 2. DETAILED DESCRIPTION
[0032] The present application is further described below in conjunction with specific embodiments.
[0033] It should be noted that the terms such as "upper", "lower", "left", "right", "middle", etc. cited in this specification are only for the convenience of description and are not used to limit the scope of implementation. Changes or adjustments to their relative relationships should be regarded as the scope of implementation of this application without substantially changing the technical content.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.
[0035] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0036] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.
[0037] As used herein, the term "at least one of" is intended to be synonymous with "one or more of." For example, "at least one of A, B, and C" expressly includes only A, only B, only C, and combinations of each thereof.
[0038] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.
[0039] As a new type of polymer, polyaspartic acid solution can react with multivalent positive ions in a crosslinking agent solution to form a gel material. The present invention uses sodium polyaspartate to compound benzotriazole, sodium benzoate, and sodium citrate to prepare a vapor phase corrosion inhibitor, which is coated on the surface of a substrate to form a gel layer through crosslinking by multivalent positive ions in the crosslinking agent solution. After drying, a vapor phase rust-proof product is obtained, which is used for rust prevention of metal materials, such as Figure 1 shown.
[0040] In the following examples, kraft paper is used as the substrate.
[0041] Embodiment 1
[0042] Vapor phase corrosion inhibitor: 100g, including:
[0043] Sodium polyaspartate 20g
[0044] Benzotriazole 2g
[0045] Sodium benzoate 5g
[0046] Sodium citrate 3g
[0047] 70g water
[0048] Embodiment 2
[0049] Vapor phase corrosion inhibitor: 100g, including:
[0050] Sodium polyaspartate 20g
[0051] Benzotriazole 2g
[0052] Sodium benzoate 5g
[0053] Sodium citrate 3g
[0054] 70g water
[0055] Cross-linking agent solution: 10 wt% calcium chloride solution (10 g) Example 3
[0056] Vapor phase corrosion inhibitor: 100g, including:
[0057] Sodium polyaspartate 20g
[0058] Benzotriazole 2g
[0059] Sodium benzoate 5g
[0060] Sodium citrate 3g
[0061] 70g water
[0062] Cross-linking agent solution: 10 wt% zinc chloride solution (10 g) Example 4
[0063] Vapor phase corrosion inhibitor: 100g, including:
[0064] Sodium polyaspartate 20g
[0065] Benzotriazole 2g
[0066] Sodium benzoate 5g
[0067] Sodium citrate 3g
[0068] 70g water
[0069] Crosslinking agent solution: 10wt% barium chloride solution (10g)
[0070] Embodiment 5
[0071] Vapor phase corrosion inhibitor: 100g, including:
[0072] Sodium polyaspartate 20g
[0073] Benzotriazole 2g
[0074] Sodium benzoate 5g
[0075] Sodium citrate 3g
[0076] 70g water
[0077] Cross-linking agent solution: 10 wt% aluminum chloride solution (10 g).
[0078] The method for preparing a gas phase rust-proof product using the gas phase corrosion inhibitor of each embodiment comprises the following steps:
[0079] S1, dissolving sodium polyaspartate, benzotriazole, sodium benzoate and sodium citrate in water by stirring to prepare a vapor phase corrosion inhibitor liquid, and setting aside;
[0080] S2, first coating: The first coating is performed on the kraft paper substrate using the above-mentioned vapor phase corrosion inhibitor by roller coating, and the coating amount of the vapor phase corrosion inhibitor is 46g / m 2 .
[0081] S3, after the first coating is completed, the second coating is carried out by spraying the crosslinking agent solution on the surface of the vapor phase corrosion inhibitor. The coating amount of the crosslinking agent solution is 12g / m 2 .
[0082] S4, after the second coating is completed, the vapor phase rust-proof product is naturally dried. Calculated by dry weight, the total coating amount of the vapor phase corrosion inhibitor and the cross-linking agent after drying is 15g / m 2 .
[0083] The protective effect of vapor phase rust-proof products (rust-proof paper) prepared by cross-linking the same vapor phase corrosion inhibition liquid on the substrate kraft paper with different cross-linking agents on carbon steel was verified by the static weight loss method. The test conditions were 60±1℃ and 90% humidity. The weight loss results after 24 hours, 48 hours and 72 hours of accelerated corrosion are shown in Table 1.
[0084] Table 1
[0085]
[0086]
[0087] Example 1 is an application case of vapor phase anti-rust paper without using a cross-linking agent, and Examples 2 to 5 are application cases of vapor phase anti-rust paper using calcium chloride, zinc chloride, barium chloride, and aluminum chloride solutions for cross-linking treatment, respectively. Regardless of which multivalent cationic cross-linking agent is used, the carbon steel samples tested show a good corrosion inhibition effect compared to the vapor phase anti-rust paper products without using a cross-linking agent, and the weight loss rate is less than 0.2%, which fully verifies the practical application effect of the present technical solution.
[0088] The present invention forms a network structure through the ionic interaction between the carboxyl anions of polyaspartic acid and the multivalent positive ions, with high crosslinking density and strong compactness. The vapor phase corrosion inhibitor prepared in Example 1 is coated on kraft paper without crosslinking treatment, and the vapor phase corrosion inhibitor prepared in Example 2 is coated and crosslinked with calcium chloride solution. The surface morphologies of the two after drying are as follows: Figure 2 The results of scanning electron microscopy (SEM) are shown in (A) and (B). Figure 2 As can be seen from (A), the uncrosslinked vapor phase corrosion inhibitor is distributed in powder form on the substrate surface, while Figure 2 It can be seen from (B) that the surface of the vapor phase corrosion inhibition layer cross-linked by calcium chloride solution is dense, has no obvious pores, and is continuously distributed.
[0089] The test results of the anti-rust effect of the gas phase anti-rust products prepared by the present invention are as follows: Figure 3 As shown, Figure 3 (A) is a carbon steel test sample wrapped with kraft paper as the base material. Figure 3 (B) in the figure is a carbon steel test sample wrapped with vapor-phase anti-rust paper prepared by coating the vapor-phase corrosion inhibitor prepared in Example 2. After being stored in the same environment for 6 months, the test carbon steel sample was taken out. From the surface corrosion of the carbon steel sample, it can be seen that the surface of the carbon steel sample wrapped with the substrate kraft paper is seriously corroded, while the vapor-phase anti-rust paper prepared by coating the vapor-phase corrosion inhibitor prepared in Example 2 has a very protective effect on carbon steel. After storage for 6 months, the surface is still smooth and no rust spots are seen.
[0090] The above-mentioned implementation cases are only preferred implementation cases in the present invention, but the implementation methods of the present invention are not limited to the above-mentioned implementation cases. For example, various forms of combinations of the schemes in the embodiments, any other changes, modifications, substitutions, and combinations made without departing from the spirit and principles of the present invention should be equivalent replacement methods and are within the protection scope of the present invention.
Claims
1. A cross-linked polyaspartic acid vapor phase corrosion inhibitor, characterized in that: The gas phase corrosion inhibitor comprises a gas phase corrosion inhibitor solution and a cross-linking agent solution. The raw materials for preparing the vapor phase corrosion inhibitor include the following components based on 100 parts by weight: Sodium polyaspartate 10-50 parts 1-5 parts of benzotriazole Sodium benzoate 1-10 parts Sodium citrate 1-10 parts Water balance; The cross-linking agent solution is a soluble multivalent metal salt solution.
2. The vapor phase corrosion inhibitor according to claim 1, characterized in that The metal in the soluble metal salt solution is any one of aluminum, calcium, barium and zinc, preferably calcium.
3. The vapor phase corrosion inhibitor according to claim 1, characterized in that The soluble metal salt solution is any one of calcium chloride solution, zinc chloride solution, barium chloride solution and aluminum chloride solution.
4. The vapor phase corrosion inhibitor according to claim 1, characterized in that The mass concentration of the soluble metal salt solution is 0.1-30%.
5. A vapor phase rust-proof product, characterized in that: On the substrate, a first coating is performed with the vapor phase corrosion inhibitor liquid of any one of claims 1 to 4, and then a second coating is performed with a crosslinking agent solution and then dried to obtain the vapor phase rust-proof product.
6. The vapor phase rust-proof product according to claim 5, characterized in that: The substrate is any one of kraft paper, paper tray, fiberboard and non-woven fabric.
7. A method for preparing a vapor phase rust-proof product based on the vapor phase corrosion inhibitor according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1, dissolving sodium polyaspartate, benzotriazole, sodium benzoate and sodium citrate in water by stirring to prepare a vapor phase corrosion inhibitor solution, and setting aside; S2, first coating: applying the first coating of the vapor phase corrosion inhibitor on the substrate; S3, after the first coating is completed, a soluble divalent or trivalent metal salt solution is used as a cross-linking agent solution to perform a second coating on the surface of the vapor phase corrosion inhibition liquid; S4, after the second coating is completed, the vapor phase rust-proof product is naturally dried or baked, wherein the dry weight ratio of the vapor phase corrosion inhibitor solution to the crosslinking agent solution is 10-20:1, and the total coating amount of the two is 10-30g / m 2 , more preferably 15g / m 2 .
8. The method according to claim 7, characterized in that The first coating is done by dipping, rolling, spraying or showering.
9. The method according to claim 7, characterized in that The second coating is done by spraying or pouring.
10. Use of the vapor phase rust-proof product according to claim 5 or 6 for rust prevention of metal materials.
